Language and Communication Development of Students with Hearing Problems in Special Needs Schools - Saputra, Ahmad Yudi; Hadi, Ade Sopyan; Hamdi, Zulfadli (International Journal of Pedagogy and Learning Community (IJPLC), 2024)
Language and speech are tools for communication. Language and communication problems are particularly evident in students with hearing and speech problems. This research aims to find out the hearing and speech problems of hearing-impaired students from the aspects of phonology, morphology, syntax, semantics, and pragmatics. Three theories are closely related to communication, language, and speech. First are behaviorism theory, nativism theory, and interactionalism theory. This study uses a design-shape research case that uses a qualitative approach to explain and describe language and speech errors among students with more profound hearing problems. Results from the analysis of the findings acquired, that the research almost answered the questions by using three types of instruments: interview anecdotal records, and even checklists. Through all three methods, we can conclude that the student's hearing becomes increasingly bad, and it becomes more and more difficult for him to speak well. Students who have level hearing which is light and simple can speak if given intervention regularly while students with severe or relatively severe hearing need to get treatment immediately. Collaboration with parents also plays an important role in helping the student with hearing problems in dealing with disability. Continuous education at home and at school have positive impacts on the students.